Microstructural reorganization and cargo release in pyrene urethane methacrylate random copolymer hollow capsules - Kaushlendra, K.; Asha, S. K. (Langmuir, 2012)
We report the synthesis of polymer microcapsules by direct one-pot free radical random copolymerization approach. Urethane methacrylate comb monomers having pendant pyrene (Py) and 3-pentadecyl phenol (PDP) units were copolymerized in a random manner using benzoyl peroxide (BPO) as free radical initiator in dimethylformamide (DMF) as solvent. These copolymers and corresponding homopolymers spontaneously self-organized into microspheres upon drop casting from solvents like DMF and tetrahydrofuran (THF). Stable microspheres were obtained in water by dialyzing THF solution of the polymers against water in dialysis bags with molecular weight cutoff of similar to 2000. The hollow nature of the spheres was confirmed by rhodamine B (RhB) encapsulation followed by Forster resonance energy transfer (FRET) based fluorescence emission from RhB upon exciting pyrene. The microenvironment inside the capsule was probed by following the I-1/I-3 ratio of pyrene emission as well as RhB release as a function of temperature. The RhB encapsulated in the pyrene homopolymer PIHP-100Py capsules experienced strong donor-acceptor interaction and did not undergo complete release even at high temperature (85 degrees C). The encapsulated RhB from the copolymers with low pyrene incorporation was released almost fully upon heating beyond 50 degrees C. Pyrene moieties in the PIHP-100Py were shielded from surrounding water and experienced a hydrophobic environment, whereas in the low pyrene incorporated copolymer the PDP units were better shielded from the hydrophilic environment. This work represents a simple approach to produce polymer hollow capsules, and the varying pyrene incorporation was used to trace the microenvironment inside the capsules.